Analysis of Intellectual Capital and Organizational Culture on Employee Performance in Creative Industry Wedding Organizer Surabaya City - Putri Tasya Nabillah; Gendut Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to examine how organizational culture and intellectual capital affect employee performance in Surabaya City's creative wedding organizer sector. This study employs a quantitative methodology. Data collection to be used in this research is through the use of questionnaires and a Likert scale of 1 to 5 in the scoring calculation of the questionnaire. The sampling method used in this research is the purposive sampling method, and we obtained five wedding organizer businesses in Surabaya City with a sample of 56 respondents determined using the Slovin formula. The data were analyzed using Partial Least squares (PLS). The findings of this study demonstrate that the variable of organizational culture has a favorable and significant impact on worker performance. Employee performance is positively and significantly impacted by the intellectual capital variable. Of the three aspects of intellectual capital, the structural capital component is more prominent than the human capital and relational capital dimensions.